An international survey on canine urinary incontinence: case frequency, diagnosis, treatment and follow-up - Falceto, M. V.; Caccamo, R.; Garrido, A. M.; Pisu, M. C.; Tejedor, M. T.; Trerotoli, P.; Nicoli, S.; Zagarella, P.; Lippi, I.; García-Pedraza, E.; Rambaldi, J.; Kirilova, D.; et al. (Frontiers in Veterinary Science, 2024)
Urinary incontinence (UI) consists of involuntary leakage of urine during the storage phase of urination. An anonymous survey was given to Spanish and Italian veterinarians about canine UI treated cases, diagnosis, treatment, follow-up, and professional interest. Most veterinarians treated ≤3 cases/quarter, resulting in the percentage of incontinence males being lower than that of females (1-4% vs 0-24%). The percentage of spayed incontinent females was lower in Spain (0-24%) than in Italy (75-100%). Most diagnoses were based on a diagnostic algorithm (Spain: 88.7%; Italy: 65.3%); patient report and history, blood work, urinalysis and abdominal ultrasound. Urethral/bladder pressure measurement was unusual (Spain: 0.2%; Italy: 2.4%). In Spain, radiology with contrast medium and CT urography (26.3% and 34.4%, respectively) were more frequent than in Italy (11.6% and 22.7%, respectively). When suspecting urethral sphincter mechanism incompetence (USMI), most of the respondents started a pharmacological trial (Spain: 93.2%; Italy: 78.9%). The first-choice medical treatment was Phenylpropanolamine, followed by Ephedrine and Deslorelin. When pharmacotherapy failed, the most frequent option was drug change, followed by increased drug dosage/frequency of administration, surgical therapy and colposuspension. A review was completed after the first week of treatment followed by periodic reviews. Most of the respondents participated in continuing education only if UI occurred in their everyday practice (Spain: 63.0%; Italy: 55.4%) and about 30% responders did it regardless of the number of UI cases treated (Spain: 30.5%; Italy: 37.4%). Some recommendations in clinical practice were made. UI can be underestimated by owners; therefore, a complete history should be obtained by veterinarians. Veterinarians should carefully evaluate if spaying is advisable considering it could increase UI risk. A step-by-step approach is recommended and a specific diagnostic-therapeutic algorithm for UI in dogs is provided. Conservative approaches (regular exercise, weight loss in overweight dogs and observing an "incontinence diary" to identify abnormal patterns of urination) are advisable.